The Influence of Price, Product Completeness, and Ease of Use of the Bukalapak Application on Purchase Decisions on the Bukalapak Application in Mataram City - Hastati, Ayu (International Journal of Economics Studies, 2025)
This study aims to analyze the influence of price, product completeness, and ease of use of the Bukalapak application on purchasing decisions in Mataram City. With the rise of online shopping trends, it is important to understand the factors that influence consumers' decisions in choosing an e-commerce platform. This study uses a quantitative method with data collection through questionnaires distributed to Bukalapak users in Mataram. The results of the analysis show that price has a significant influence on purchasing decisions, where consumers tend to choose products at prices that match the quality offered. In addition, product completeness also plays an important role, because the variety of product choices provides flexibility for consumers to choose according to their needs. The ease of use of the app is another factor that is no less important; An easy-to-use app increases user convenience and encourages them to make purchases. Overall, this study provides valuable insights for business actors in Bukalapak to improve their marketing strategies by considering the factors that influence consumer purchasing decisions. These findings are expected to help increase customer satisfaction and loyalty.